Exploring Computational Methods to Advance Clinical Decision Making - Kiril Tenekedjiev; Mike Calford (Applied Sciences)
The papers comprising our Special Issue on advanced decision making in clinical medicine (which is part of the series in applied bioscience and bioengineering) were conceived and written during a most challenging time for medical science and its delivery—the COVID-19 pandemic [...]